PERBEDAAN KUALITAS HIDUP KLIEN MELALUI PROGRAM REHABILITASI DI KLINIK BNN KOTA CIMAHI - Gumiyarna, Hana; Syafni, Febrinaldy; Saepullah, Ridwan (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2022)
The impact of drug abuse threatens not only the survival and future of its abusers, but also the future of the nation and state. Rehabilitation Program is one of the efforts in suppressing drug abusers so that there is no more supply that continues to increase, where to measure one of its effectiveness is to measure the indication of the quality of life of the client. This study aims to determine the difference in the value of quality of life of drug rehabilitation clients from various domains before and after undergoing outpatient rehabilitation at the clinic pratama BNN Cimahi. The research method in this study is a quantitative research with a comparative method audience, where the population is all clients of the outpatient rehabilitation of the BNN pratama Clinic Cimahi City in 2021 as many as 30 clients, while the sample is the total of the population (total population sampling). Data analysis using T test with computer software. There is a significant difference (p=0.000) quality of life physically, there is a significant difference (p=0.005) quality of life psychologically, there is a significant difference (p=0.002) quality of life socially and there is a significant difference (p=0.001) quality of life in the overall environment before and after undergoing outpatient rehabilitation program in BNN Cimahi. there is a gradual improvement in the quality of life, but not massively terhaap quality changes hidip clients. The need for consistency and support system after undergoing rehabilitation program in maintaining the quality of life of the client even to improve towards a much better